Structural health monitoring using time reversal and cracked rod spectral element. (15th October 2016) - Lucena, R.L.; Dos Santos, J.M.C.
Abstract: Structural health monitoring (SHM) has received substantial attention in the last decades. Damage detection methods based on dynamic analysis seem to be appropriate to detect large damages, but fail for small ones. Alternative methods use elastic wave propagation allowing a quick and long range test. In this paper, a new approach based on the combination of Time Reversal Method (TRM) and Spectral Element Method (SEM) is proposed to perform structural damage detection. The main novelty is to combine wave-based spectral element model together with time reversal signal processing. Although the methodology is evaluated by numerical simulation, this combination of numerical modeling and time reversal signal processing can be applied as an experimental approach to provide a useful tool for damage detection. Simulated examples of the damage detection method using rod-like structures are illustrated and the results discussed and compared with those from literature. Abstract : Highlights: New baseline free SHM approach to detect structural damage. Wave-based modeling (SEM) is combined with time reversal technique. Very good results with simulated examples encourage experimental applications. Issues related with signal processing are raised and corrections are proposed. MATLAB codes to implement the method are provided.